Strategi Bank Nagari untuk 5 (Lima) Tahun Kedepan (2025-2030) - Rusdi Rusdi; Syafwandi Syafwandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to formulate a development strategy for Bank Nagari for the next five years (2025–2030) based on SWOT analysis. Bank Nagari, as the Regional Development Bank (BPD) of West Sumatra, plays a strategic role in driving regional economic growth, improving financial inclusion, and supporting MSMEs. Using a qualitative descriptive approach, this study identifies internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence Bank Nagari's performance. The analysis results in several priority strategies, including service digitalization, technology-based product diversification, strategic partnerships with local governments and the private sector, and strengthening governance based on Good Corporate Governance (GCG) principles. The implementation of these strategies is expected to enhance competitiveness, expand market share, and strengthen Bank Nagari's role as a driver of regional economic growth.